2020
DOI: 10.7150/jbji.44815
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Cell Count Poorly Predicts Septic Arthritis in the Presence of Crystalline Arthropathy

Abstract: Abstract. Introduction: A synovial cell count greater than 50,000/mm3 is the threshold most commonly used to diagnose septic arthritis. This lab value may be nonspecific in the setting of crystalline arthropathy. The purpose of this study was to evaluate the accuracy of diagnosing septic arthritis using a synovial cell count cut-off of 50,000/mm3 in the setting of crystalline arthropathy.Methods: This was a retrospective review of joint aspirations performed between July 1st, 2013 and June 30th, 2016. Synovial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…From a different perspective, McGillicuddy et al[ 21 ] showed that a synovial WBC count was less than 50,000/mm3 in 39% of the SA patients in their series. Similarly, Luo et al[ 12 ] found that 38.8% of the patients with SA had a synovial WBC count of <50,000/mm 3 . Li et al[ 22 ] also found that 36% of their patients with SA had a joint WBC count less than 50,000/mm 3 .…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…From a different perspective, McGillicuddy et al[ 21 ] showed that a synovial WBC count was less than 50,000/mm3 in 39% of the SA patients in their series. Similarly, Luo et al[ 12 ] found that 38.8% of the patients with SA had a synovial WBC count of <50,000/mm 3 . Li et al[ 22 ] also found that 36% of their patients with SA had a joint WBC count less than 50,000/mm 3 .…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, culture results were chosen as diagnostic criteria after the exclusion of contaminated cultures, consistent with previous studies. [ 12 , 20 , 33 ] In some studies, the diagnostic criteria were the presence of pus or Newman criteria. [ 12 , 17 ] However, using these criteria, patients who do not actually have SA would be considered as SA and, therefore, the gold standard is the culture result.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations